Assessing the environmental impacts of urban sprawl on vegetation cover and ecosystem integrity in Wa municipality, Ghana - Justice Aduko; Mohammed Aminu Yakubu; Kwame Anokye (World Development Sustainability)
This study examines the environmental implications of urban sprawl on biodiversity conservation in Wa Municipality, Ghana, with particular emphasis on the reduction of vegetation cover due to the expansion of built-up areas. Using a combination of remote sensing, Geographic Information System (GIS) techniques, and household surveys, the research analyzes land cover changes between 1986 and 2018 to assess the extent to which urban growth has contributed to ecological degradation. The findings reveal a significant increase in built-up areas, primarily at the expense of open and riparian woodlands, leading to the fragmentation and loss of habitats essential for native species. The study further identifies key drivers of urban sprawl—including population growth, housing demand, and institutional weaknesses—which have collectively intensified pressure on natural ecosystems. Local perceptions and field observations also confirm a noticeable decline in biodiversity, such as reduced tree species, wildlife presence, and natural vegetation cover. Through linking spatial urban expansion patterns directly to ecological impacts, this study highlights the urgent need for sustainable land use planning and biodiversity-sensitive urban development in Wa Municipality.